Insight and Inference : Descartes's Founding Principle and Modern Philosophy - Miles, Murray Lewis (Book collections on Project MUSE., 1999)
In this major re-examination of Descartes's founding principle, cogito, ergo sum, Murray Miles presents a portrait of Descartes as the Father of Modern Philosophy that is very different from the standard one. Viewing Descartes in both a historical and a systematic perspective, Miles presents a wealth of original analyses, arguments, and reinterpretations of key texts. The result is a fresh and illuminating account of Descartes's metaphysical project and theory of the mind. Descartes's achievement is a radical reversal of the order of knowing, a subjectivism that places knowledge of the mind ahead of knowledge of material things, yet is free of the metaphysical idealism that some of his successors went on to embrace.